2001
DOI: 10.1074/jbc.m101177200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis and Fas Receptor/Fas Ligand Expression by Ischemia/Reperfusion in Cardiac Myocytes Requires Serine 727 of the STAT-1 Transcription Factor but Not Tyrosine 701

Abstract: Previously we reported that ischemia results in apoptosis and is accompanied by phosphorylation on Tyr-701 and increased expression and transcriptional activity of the signal transducer and activator of transcription-1 (STAT-1). In the present study, we show that exposure of cardiomyocytes to ischemia induced the phosphorylation of STAT-1 at another site, Ser-727. Moreover, STAT-1 is critical for the induction of Fas receptor and Fas ligand expression by ischemia/reperfusion (I/R). Transcriptional activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
157
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(169 citation statements)
references
References 37 publications
(49 reference statements)
12
157
0
Order By: Relevance
“…Potential proapoptotic and significant prosurvival effects of STAT1 have been described previously (Shen et al, 2001;Stephanou and Latchman, 2003;Terui et al, 2004). Both effects were attributed to the ability of STAT1 to activate expression of either proapoptotic (Kumar et al, 1997;Stephanou et al, 2000Stephanou et al, , 2001 or prosurvival proteins (Stephanou et al, 1999;Madamanchi et al, 2001;Terui et al, 2004). We found here that in WT cells serine-phosphorylated STAT1 promotes cell survival through the regulation of expression of two known prosurvival genes, MCL-1 and HSP27 (Kabakov et al, 2003;Michels et al, 2005).…”
Section: Stat1 Is a Prosurvival Factor In Wilms' Tumorsupporting
confidence: 80%
“…Potential proapoptotic and significant prosurvival effects of STAT1 have been described previously (Shen et al, 2001;Stephanou and Latchman, 2003;Terui et al, 2004). Both effects were attributed to the ability of STAT1 to activate expression of either proapoptotic (Kumar et al, 1997;Stephanou et al, 2000Stephanou et al, , 2001 or prosurvival proteins (Stephanou et al, 1999;Madamanchi et al, 2001;Terui et al, 2004). We found here that in WT cells serine-phosphorylated STAT1 promotes cell survival through the regulation of expression of two known prosurvival genes, MCL-1 and HSP27 (Kabakov et al, 2003;Michels et al, 2005).…”
Section: Stat1 Is a Prosurvival Factor In Wilms' Tumorsupporting
confidence: 80%
“…We have shown that STAT-1 is expressed at enhanced levels following ischaemia/reoxygenation and is phosphorylated on tyrosine 701 and serine 727. 10,11 Moreover, inhibition of STAT-1 expression using an anti-sense approach protects the cardiac cells from apoptosis induced by ischaemia/reoxygenation. 10 To probe further the features of STAT-1 required for stress-induced apoptosis we have used the U3A cell line which lacks functional STAT-1.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] For example, overexpression of STAT1 enhances apoptotic cell death in cardiac myocyte after ischemia-reperfusion, but STAT1 antisense manipulation reduces apoptosis and decreases STAT1-induced caspase 1 and apoptotic gene (FAS, FASL) promoter activity. 21,22 Further, overexpression of STAT1 inhibits the promoter activity of anti-apoptotic genes Bcl-2 and Bcl-XL . 23 STAT1 also induces apoptosis through interacting with p53 and enhanced expression of p53-regulated genes.…”
mentioning
confidence: 99%